Implementing Go Pregnancy Exercise (GOPEX) application to improve the knowledge for building healthy pregnant women - Marfuah, Dewi; Nurjanah, Ineu; Putri, Anggela Amelia; Permana, Sholihah Al Noor; Dewi, Riri Mulyana; Nuswantoro, Bangun (Universitas Negeri Yogyakarta, 2024)
One way to prevent complications from childbirth is to do physical activity. The health status of the mother during pregnancy needs to be considered from the beginning of pregnancy, because doing regular and directed physical activity can maintain the health of the mother and fetus during pregnancy. Exercise is one of the physical activities so that pregnant mothers stay healthy and fit. There is still a lack of pregnant women to exercise due to various factors, one of which is a lack of knowledge, so health education is needed to improve their knowledge. This community service was carried out in Padamukti Village, Solokanjeruk, Bandung Regency, with a total of 37 pregnant women. This activity consists of 3 stages, namely preparation, implementation, and evaluation. The health education provided is knowledge about exercise in pregnancy using the Go Pregnancy Exercise (GoPEx) application media. This activity lasted for 90 minutes and was carried out pre- and post-test to assess the difference in the level of knowledge before and after the provision of education. There was a mean difference in knowledge's score between before and after giving the health education by the Go Pregnancy Exercise (GoPEx) Application (p-value <0.05). Pregnant women's knowledge increases after being given a health education. It is necessary to intensify the socialization of the use of the GoPEx application to increase the physical activity of pregnant women to realize healthy pregnant women.